Synthesis of Avocado Seeds Into Biodiesel Using A Catalyst CaO From Blood Cockle Shell - Suprihatin; Alif Julian; Muhammad Fikri (Science and Technology Research Centre Universitas PGRI Semarang, 2024)
Biodiesel is an environmentally friendly fuel made from oil vegetables that contain triglycerides. Biodiesel from avocado seed vegetable oil in Indonesian agricultural areas which according to BPS 2022 data, Indonesia produces 183,000 tons of avocados per year. This research aims to gained the effect of adding reaction temperature and Oil : Methanol ratio influence on biodiesel production. The avocado seed oil obtained by soxhlet extraction method, where 50 gram avocado seeds powder extracted with n-hexane solvent in 1 hour extraction time and 60℃ temperature giving result 10% yield of avocado seed oil . The CaO catalyst are obtained from Calcination procees of blood cockle shells in 900℃ temperature and 4 hours calcination time giving 98.82% CaO Cotent. The biodiesel is produces with 97% methanol reactant and 98.82% CaO catalyst in various methanol volume (30; 40; 50; 60; and 70 ml) and under different temperature conditions (30; 40, 50, 60, and 70 ℃). The best result of transesterification process biodiesel is obtained in 50℃ and 40ml methanol gets biodiesel yield of 96%, methyl ester content of 99.83%, density of 865 gr/cm3, viscosity of 2.5 cSt , mgKOH/gr acid number of 0.56 of, and heating value of 9871.6 kcal/kg. Based on the high result of methyl ester content and heating value of biodiesel obtained from the procees, the avocado seed oil biodiesel potentially used as an sustainable energy.